The Relationship Between Critical Thinking and Achievement in Social Studies Among Fifth Grade Students (A Field Study in Aleppo) - ولاء نضال منون; لينا بدور; أحلام ياسين (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of this research was to investigate the level of critical thinking and the level of achievement in social studies among fifth-grade students, and to identify the relationship between them. To achieve this goal, a descriptive approach was used. A "Critical Thinking Test" and an "Achievement Test in Social Studies" were prepared, and after verifying the validity and reliability of both tests, they were applied to a sample consisting of 240 male and female students from the fifth grade in Aleppo for the academic year 2023/2024. The results showed that the level of critical thinking among the research sample was average regarding the total score of the test and for each dimension represented by (identifying assumptions, interpretation, conclusion, inference, and evaluation of arguments). The results also revealed that the achievement level in social studies was average concerning the total score and Bloom’s lower levels, while the achievement level was low concerning Bloom’s higher levels. Furthermore, a significant correlational relationship was found between students’ scores on the critical thinking test and their scores on the achievement test, indicating a positive correlation.